2016
DOI: 10.1097/olq.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of a Diagnosis of Sexually Transmitted Infection Among Young Aboriginal and Torres Strait Islander People

Abstract: In the first community-based survey of this population, a self-reported history of ever being diagnosed as having prevalent STIs was common in sexually active young Aboriginal people who reported STI testing in the past. This population requires targeted education and health service interventions to address the high burden of STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In contrast, there were very few reported cases of mouth-anus oral sex as well as anal sex. Such data are similar to data from another study where higher percentages were found for vaginal intercourse [24], or where oral sex was more frequent than anal sex [18]. Our findings with respect to a higher frequency of vaginal sex as opposed to anal sex may be conditioned by mostly heterosexual subjects in our sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, there were very few reported cases of mouth-anus oral sex as well as anal sex. Such data are similar to data from another study where higher percentages were found for vaginal intercourse [24], or where oral sex was more frequent than anal sex [18]. Our findings with respect to a higher frequency of vaginal sex as opposed to anal sex may be conditioned by mostly heterosexual subjects in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…In relation to condom use, results show an inconsistent use when asking subjects about the time elapsed from the last time they had sex without using a condom, which could increase contagion and transmission of STIs. It is worth mentioning that evidence is firm when relating the low use of condom to a higher risk of getting an STI [ 13 , 24 , 26 , 27 ]. In general, the epidemiological studies available has shown that, when condoms are used constantly and correctly, they are highly effective to prevent HIV infection and they reduce the risk of other STIs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to risk indicators, we have found that drug use becomes a risky practice for transmission of STIs, due to the limitation imposed on the individual’s decision-making capability, making them more vulnerable, as pointed out by other authors [ 33 , 47 , 48 ]. Evidence associates the low use of condoms with a higher risk of STI contagion [ 49 , 50 , 51 , 52 ], in line with our results, despite some nuances. We have analyzed the time period elapsed since the last time a condom was used and not its frequency of use, but literature identifies both factors as strongly associated with a significant risk of acquiring an STI [ 22 , 24 , 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…STI notifications in Aboriginal populations in Australia occur at a higher rate in young people aged 15–29 years than in the corresponding age bracket in the non‐Indigenous population 18 . The most common STI diagnosis in Aboriginal young people across Australia is chlamydia, followed by gonorrhoea and syphilis 19 . HIV prevalence in the Aboriginal population remains low, 20 but the HIV notification rate for Aboriginal people has increased in recent years while simultaneously decreasing in the non‐Indigenous Australian‐born population 18…”
Section: Epidemiological Contextmentioning
confidence: 99%